The environmental crisis: A religious solution? - Hugo, Leon; Hugo, Jean O. (Koers (Potchefstroom, South Africa), 2025)
The earth and its inhabitants are facing an impending environmental catastrophe. Despite remarkable technological advancements and sophisticated economic strategies, the situation continues to worsen at an alarming rate. The growing demand for higher living standards exacerbates the exploitation of resources, contributing to environmental degradation. Human greed and interpersonal competition drive the rapid extraction of natural resources, leading to the degradation of the planet’s ecological foundation. Therefore, the solution does not lie in enhanced or restrained technological progress, educational programmes or new economic theories but in transforming human attitudes and aspirations, profoundly shaped by socio-economic and cultural-historical contexts.In this context, religion plays a crucial role in shaping individuals’ worldviews. Most religious teachings advocate for the responsible use of resources, together with love and respect towards other human beings. If these core principles of environmental stewardship and care for others, along with the warnings against greed and the dangers of wealth, were more actively embraced, the current environmental crisis could have been avoided.